2016
DOI: 10.1172/jci.insight.80749
|View full text |Cite
|
Sign up to set email alerts
|

Trimeprazine increases IRS2 in human islets and promotes pancreatic β cell growth and function in mice

Abstract: The capacity of pancreatic β cells to maintain glucose homeostasis during chronic physiologic and immunologic stress is important for cellular and metabolic homeostasis. Insulin receptor substrate 2 (IRS2) is a regulated adapter protein that links the insulin and IGF1 receptors to downstream signaling cascades. Since strategies to maintain or increase IRS2 expression can promote β cell growth, function, and survival, we conducted a screen to find small molecules that can increase IRS2 mRNA in isolated human pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Ablation of IRS2 in whole pancreas caused β-cell mass decrease with reduced β-cell proliferation in the mouse model (Cantley et al 2007). Agents able to upregulate IRS2 may promote β-cell function under physiological stress during T2DM progression (Kuznetsova et al 2016). Currently, our result has clearly demonstrated that vincamine as an upregulator of IRS2 expression in vivo and in vitro efficiently improved β-cell function, which further supported the key role of IRS2 in β-cells.…”
Section: Hfd/stzsupporting
confidence: 70%
See 1 more Smart Citation
“…Ablation of IRS2 in whole pancreas caused β-cell mass decrease with reduced β-cell proliferation in the mouse model (Cantley et al 2007). Agents able to upregulate IRS2 may promote β-cell function under physiological stress during T2DM progression (Kuznetsova et al 2016). Currently, our result has clearly demonstrated that vincamine as an upregulator of IRS2 expression in vivo and in vitro efficiently improved β-cell function, which further supported the key role of IRS2 in β-cells.…”
Section: Hfd/stzsupporting
confidence: 70%
“…As IRS2/PI3K/Akt signaling has been indicated to be involved in the vincamine-mediated β-cell protection and a published report has indicated that IRS2 is mediated by cAMP or Ca 2+ -regulated transcription factors in β-cells (Kuznetsova et al 2016), we next investigated whether regulation of vincamine involved these two second messengers in INS-832/13 cells.…”
Section: Camp and Ca 2+ Participate In Vincamine Protecting Against Smentioning
confidence: 99%
“…IRS2 expression through these mechanisms maintains PDX1 action, which is essential for β-cell growth, function, and survival ( Figure 5 ) [ 98 ]. Compounds that augment IRS2 expression may be useful for treatment of β-cell failure during insulin resistance and the progression of T2DM [ 99 ].
Figure 5 The integrative role of IR/IGF1R→IRS2 signaling in pancreatic β-cell function.
…”
Section: Insulin Action In Non-classical Target Tissues As Revealed By Gene Knockoutmentioning
confidence: 99%
“…This can be useful in designing treatment strategies for certain cancers as mentioned above but also for inflammatory diseases and diabetes in which IL-4 and insulin play an important role. Several strategies to increase expression of IRS2 with pharmacologic agents are being explored to enhance pancreatic β-cell and endothelial cell survival in the context of Type II diabetes ( 18 , 95 ). However, our current understanding of the relative roles of IRS1 and IRS2 in mediating and modulating allergic diseases is quite limited.…”
Section: Contribution Of Irs Proteins To Cell Survivalmentioning
confidence: 99%
“…What about IRS1? Targeting strategies are just beginning to be explored and developed in the context of epithelial cancers and Type II diabetes ( 18 , 80 , 95 ). What about allergic disease?…”
Section: Future Studiesmentioning
confidence: 99%